Quality of life, health conditions and life style of civil police officers - Francis Ghignatti da Costa; Lizandra Santos Vieira; Mateus Gomes Cócaro; Karina de Oliveira Azzolin; Daiane Dal Pai; Juliana Petri Tavares
ABSTRACT Objectives: Evaluate the relation between quality of life, health conditions and life style of Civil Police Officers in Porto Alegre/RS. Method: Transversal study with 237 police officers that answered a questionnaire containing socio-occupational information, life style, health conditions and the instrument World Health Quality of Life (WHOQOL-bref). The data was collected in 2018 and submitted to statistical analysis. Results: Broad domain of quality of life showed higher rates in non-hypertensive subjects (p=0,002), without cardiovascular alterations (p=0,001), non-smokers (p=0,003), no alcohol ingestion (p=0,036), regular physical activity (p<0,001), healthy eating (p<0,001), no use of medication (p=0,028), able to have time to rest (p=0,049). Correlated with sleeping, weight, abdominal and hip circumference (p<0.01). Conclusion: Chronic diseases, use of medication and unhealthy lifestyle are related to worsening health-related quality of life.